Virtual virus - Mohammad Sopian, Abdul Jamil (2006)
Computer games have grown considerably in scale and complexity since their humble beginnings in the 1960s. Modem day computer games have reached incredible levels of realism,especially in areas like graphics,physical simulation,and artificial intelligence.However,despite significant advances in software engineering,the development of computer games generally does not employ state-ofthe-art software engineering practices and tools.The goal for this game is to reach the human-level Al real - time strategy.This system is near to reach Al that can be reacts with human,example evaluate their resource,enemy unit quantity,position,etc.This game has its own ability which the selected unit has their own advantages and disadvantages that can be used if the strategy is well-managed.